Direct kinetic assay of interactions between small peptides and immobilized antibodies using a surface plasmon resonance biosensor - Gomes, P (2002)
A surface plasmon resonance (SPR) protocol is described for the direct kinetic analysis of small antigenic peptides interacting with immobilized monoclonal antibodies (mAb). High peptide concentrations (up to 2.5 muM) and medium mAb surface densities (about 1.5 ng/mm(2)) are needed to ensure measurable binding levels, and fast buffer flow rates (60 mul/min) are required to minimize diffusion-controlled kinetics. Good reproducibility levels in the kinetic constants are obtained under these analysis conditions (standard deviations below 10% of the mean values). Application of this protocol to determine the antigenic ranking of viral peptides shows an excellent agreement between SPR and previous competition enzyme-link-ed immunosorbent assays (ELISA) on the same peptide/antibody systems.